Sturge-Weber syndrome with bilateral intracranial calcification. Issue 5 (May 1976) - Boltshauser, E; Wilson, J; Hoare, R D
Abstract : Four children affected by Sturge-Weber syndrome and demonstrating bilateral intracranial calcification are described, bringing up to 21 the number of similar reported cases. The frequency of bilateral hemisphere involvement in this syndrome is not known, but it might be as high as 15%. If present, neurosurgical intervention is, in our opinion, contraindicated.